Broadband, high-sensitivity self-powered ferroelectric LuMnO3-based photodetector with large photocurrent output. Issue 8 (15th April 2023) - Gong, Ao; Zhang, Shan; Li, Yong; Han, Pei; Lu, Chunxiao; Sun, Ningning; Zhao, Ye; Xing, Lei; Zhang, Liwen; Hao, Xihong
Abstract: The broadband spectrum detection from ultraviolet to near-infrared is hankered in the photoelectric applications of imaging, sensing and communication. Here, a new self-powered photodetector based on ferroelectric LuMnO3 thin film with a narrow bandgap of 1.46 eV exhibits high-sensitivity ultraviolet–visible–near infrared photodetection properties. The responsivity ( R ) and detectivity ( D *) in sunlight are 0.4 A/W and 7.05 × 10 11 Jones, which are much higher than that of other ferroelectric photodetectors. Moreover, under the monochromatic light (900 nm), the R and D * can reach 0.39 A/W and 6.89 × 10 11 Jones. The outstanding photodetection performances owed to the large photocurrent output, where the short-circuit current density can reach 10.5 mA/cm 2 under 1 sun illumination. The synergistic effect of ferroelectric photovoltaic effect and interface barrier effect demonstrates that the multi-driving forces can achieve high dissociation efficiency for photon-generated carriers. The excellent photodetection performances open up new application of ferroelectric materials in broadband self-powered photodetectors.